Determinants of Maternal Mortality Prevention by Midwives in Sleman Regency in 2023 - Rizqi, Anna Amalia; Djannah, Siti; Suryani, Dyah (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
The Maternal Mortality Rate serves as a gauge of maternal health quality and can also assess the level of public health, due to its sensitivity to improvements in healthcare services, both in terms of accessibility and quality. Research to find out the determinants, efforts and obstacles to preventing maternal death by midwives in Sleman Regency in 2023. This research method uses mixed methods with a sequential explanatory approach. Quantitative analysis used Chi Square bivariate analysis. The results of the study found that the factors related to the prevention of maternal death by midwives in Sleman Regency were length of work and competence. An overview of efforts to prevent maternal death by midwives in Sleman Regency, namely by carrying out ANC, keeping records, making referrals when needed, providing KIE and participating in training to upgrade knowledge, competencies and skills supported by regulations related to pregnant women's health and an innovation program called "Totality of Besti”. This research can be utilized to enhance maternal health services in Sleman Regency by improving and updating the experiences and competencies of midwives through regular training. It requires collaboration among the health department, midwives, and pregnant women to prevent maternal mortality